Radioresistance and genomic alterations in head and neck squamous cell cancer: Sub‐analysis of the ProfiLER protocol. Issue 12 (13th October 2021) - Rowinski, Elise; Magné, Nicolas; Fayette, Jérôme; Daguenet, Elisabeth; Racadot, Séverine; Pommier, Pascal; Méry, Benoîte; Vallard, Alexis; Tinquaut, Fabien; Neidhardt‐Berard, Eve‐Marie; Cassier, Philippe; Attignon, Valéry; et al.
Abstract: Background: Genome analysis could provide tools to assess predictive molecular biomarkers of radioresistance. Methods: Head and neck squamous cell carcinoma patients included in ProfiLER study and who underwent a curative radiotherapy were screened. Univariate and Cox multivariate analyses were performed to explore the relationships between molecular abnormalities, infield relapse and complete tumor response after radiation. Results: One hundred and forty‐three patients were analyzed. PIK3CA mutation and genomic instability of MAP kinases pathway were found to be prognostic factors of loco‐regional relapse in multivariate analysis with respectively HR 0.33, 95% CI 0.13–0.83, p = 0.005 and HR 0.61, 95% CI 0.38–0.96, p = 0.025. Instability of apoptosis pathway was found to be a prognostic factor of complete response after radiotherapy with HR 0.24, 95% CI 0.07–0.88, p = 0.04. Conclusion: This sub analysis suggests that PIK3CA mutation, variation of copy number of MAP kinases and apoptosis pathways play a significant role in the radioresistance phenomenon.